MENEMBUS RAHASIA BANK TERKAIT HARTA BERSAMA DALAM PERKAWINAN - Sri Harini Dwiyatmi; Indirani Wauran (Universitas Kristen Satya Wacana, 2017)
This Article discusses about bank secrecy upon joint marital property which is kept in a bank. A standpoint offered by this article leads to a statement that there is no obligation of bank to not provide a husband or a wife account information about their joint marital property. The argument is based on an idea that joint marital property is acquired during marriage, it is obtained by husband and wife who decide not to do a prenuptial agreement. As a consequence, there is no obligation of bank to keep the account secrecy in which the joint marital property is saved. This judgment lays on a reasoning that a husband or a wife who owns a bank account holds a position as the owner of the kept property in the form of bank account. Therefore, it must be understood as a norm, that a limitation on an individual’s right to have access to his/her own property shall not be applied.